Argentina: the new government and denialism - Lagos, Darío Manuel; Kordon, Diana Ruth (Torture Journal, 2023)
On 10 December, a new government took office in Argentina, the product of democratic elections. The human rights movement has dealt a blow with the victory of the representatives of the fascist extreme right, Javier Milei and Victoria Villarruel. They refer to Donald Trump, Benjamin Netanyahu, Jair Bolsonaro and some European sectors, represented by the Spanish Vox, or the Prime Minister of Italy, Giorgia Meloni among others. All of them with an agenda that backlashed human rights achievements and anti-torture work. In their proposals, Milei and Villarruel openly vindicate the genocidaires of the military dictatorship. Days before the elections, the new vice-president held an act in the Legislature of the city of Buenos Aires, the content of which was the justification of the genocidal actions of the military dictatorship (1976- 1984). Denialism of the State terrorism that took place during those years is more than an exercise of manipulation of memory; it is a political interpretation of the present that aims to influence the construction of the future.